Enterprise social network: psy-social approach in human resource management? - Školudová Jana (Mendelova univerzita v Brně, 2014)
The psycho-social approach to human resource management has developed historically out of the school of human relations. It encompasses demands on the personality of the managing workers, methods of communication, managing relationships between employees across organizational structure and methods of motivating workers to attain company goals. This report focuses on the enterprise social network and the opportunities for managers to use it as a psycho-social approach to human resource management within an organization. The report includes a brief historical outline of the development of psycho-social approaches, including a comparison of the selected theories focusing on modern trends. The goal of this report is to analyze and compare existing research/studies focused on enterprise social networks from the perspective of the psycho-social approach in human resource management and to answer the proposed research question. The report's methodology has been conducted on the basis of comparative qualitative research, empirical generalization and interpretation of the results of the research/studies. Included in the article is a discussion of the problematic of the importance of employees and the selected motivational theories.
Podniková sociální síť: psychologicko-sociální přístup v řízení lidských zdrojů?
Keywords: Enterprise social network; psycho-social approach; organization; human resources; IT management; Podniková sociální síť; psychologicko-sociální přístup; organizace; lidské zdroje; IT management